Evaluasi Green Building Berdasarkan Greenship untuk Bangunan Baru Versi 1.2 (Studi Kasus: Masjid Al-Hikmah Universitas Jember) - El Qorina Safitri, Shinta; Trisiana, Anita; Ratnaningsih, Anik (Indonesian Society of Applied Science, 2022)
To minimize the effects of global warming, there are several efforts that can be done, for example by conserving energy. In this problem, the concept of green building is the right solution to reduce global warming, especially in the scope of Civil Engineering Buildings. The Al-Hikmah Mosque at the University of Jember is a new building, with the concept of an environmentally friendly building, it is hoped that the mosque has implemented the concept of an environmentally friendly building based on GBCI standards. The research is included in quantitative descriptive research using the reference Greenship Version 1.2. The research was conducted according to the condition of the building that had passed the construction period (Final Assessment). There are 6 variables used in the study, namely the appropriate land use category (TGL), energy effectiveness and conservation (EPE), water conservation (PA), material cycle and recycling (DUM), indoor air quality (KUR), building environmental management. (PLB). Based on the results of the analysis and calculations, the Al-Hikmah Mosque at the University of Jember got a percentage of 48% or Silver, after the recommendation of a strategy to increase the rating using a SWOT analysis, the Al-Hikmah Mosque at the University of Jember got a percentage of predicates according to the building's ability, which was 61.386% or Gold. The cost required to increase the rating is Rp. 97,383,600,000.